Петр Чайковский. Места счастливого детства - Минин Рудольф Андреевич (Удмуртия, 2018)
Экземпляры: ф.15 (20200918) / Инвентарный номер: 60298 / Цена: / Сис.шифр: 85.313(2Рос.Удм) / Авт.знак: М 61 / ГРНТИ: 18.41.09 / ББК: 85.313(2Рос.Удм)^VLBC/RL